Organics abatement and recovery from wastewater by a polymerization-based electrochemically assisted persulfate process: Promotion effect of chloride ion and its mechanism - Yang, Sui-Qin; Liu, Zheng-Qian; Cui, Yu-Hong; Wang, Ming-Kui (Journal of hazardous materials, 2023)
Ubiquitous chloride ion (Cl-) in wastewaters usually inhibits the degradation of organic contaminants and generates numerous toxic chlorinated products in conventional degradation-based advanced oxidation processes (AOPs). Herein, a more Cl- tolerant polymerization-based electrochemical AOP for organic contaminants abatement and simultaneous organic resource recovery was demonstrated with eight typical organic contaminants and two real industrial wastewaters for the first time. This process can significantly promote dissolved organic carbon (DOC) abatement in the presence of Cl-, differing greatly from conventional degradation-based processes. Compared to sulfate radical (SO4•-) (or hydroxyl radical (HO•)), dichloride radical (Cl2•-) derived from Cl- has moderate reactivity towards most contaminants, which facilitates the organics polymerization as it ensures the formation of polymerizable organic radicals while inhibiting their excessive degradation. Thus, high DOC abatement (over 75 %) and high organic resource recovery ratio (48–79 % separable organic-polymer yield) can be achieved for most contaminants. Both soluble chlorinated compounds and solid chlorinated polymers are formed in the presence of Cl-. The chlorinated products (e.g. chlorophenols) can be polymerized as new monomers, thus the concentration of dissolved organic chlorinated products is much lower than that in conventional degradation-based process. The tolerance of the present process to Cl- is tested in real coking wastewaters, and exceeding 60 % of the abated chemical oxygen demand (COD) is obtained in the form of recoverable organic-polymers. [Display omitted] •Derived Cl2•- are initiators for organics polymerization in the presence of Cl-.•Moderate rate constants between Cl2•- and contaminants favor the polymerization.•Dissolved chlorinated organic products can be reduced through polymerization.•The process has high tolerance to Cl- in the real industrial wastewater treatment.•Contaminants removal and resource recovery can be achieved simultaneously.